Research on Exploiting Cognitive Hacks (REACH) - Marsili, M. (Ciência 2023, 2024)
Are you afraid of the Metaverse, its enabling technologies, and their misleading use in the information environment? Maybe you should be. Today’s world is characterized by global interconnectivity. Digital innovations are increasingly touching all aspects of life and have a profound impact on defense, security and civilian society and disrupt or overturn traditional methods and practices, and may revolutionize governmental structures, economies, and international security. This ambitious project will disclose the impact of cognitive hacks conducted through the Metaverse on European targets, i.e., individuals–the broad audience, political and military leaders, policy and decision-makers, media, and communication professionals–and society, and how international relations and may be affected by such actions and will contribute to strengthening the European identity and promote a resilient society.